2021
DOI: 10.3390/cells10051062
|View full text |Cite
|
Sign up to set email alerts
|

Weapons Evolve Faster Than Sperm in Bovids and Cervids

Abstract: In polyandrous species, males face reproductive competition both before and after mating. Sexual selection thus shapes the evolution of both pre- and postcopulatory traits, creating competing demands on resource allocation to different reproductive episodes. Traits subject to strong selection exhibit accelerated rates of phenotypic divergence, and examining evolutionary rates may inform us about the relative importance and potential fitness consequences of investing in traits under either pre- or postcopulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…Across vertebrates and in most vertebrate clades, midpiece length consistently evolves either faster or as fast as other sperm components, varying only for internal fertilizing amphibians. Narrower taxon studies in internally fertilizing species (birds, mammals, reptiles, and insects) also demonstrate that the sperm midpiece commonly evolves faster than other sperm components 18,19,[37][38][39][40] . This suggests that the sperm midpiece is under strong selection, regardless of fertilization mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across vertebrates and in most vertebrate clades, midpiece length consistently evolves either faster or as fast as other sperm components, varying only for internal fertilizing amphibians. Narrower taxon studies in internally fertilizing species (birds, mammals, reptiles, and insects) also demonstrate that the sperm midpiece commonly evolves faster than other sperm components 18,19,[37][38][39][40] . This suggests that the sperm midpiece is under strong selection, regardless of fertilization mode.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evolutionary responses in total sperm length need not be reflected in every sperm component. While the independent evolution of each sperm component may not be possible due to genetic constraints [34][35][36] , a handful of recent studies report that sperm components exhibit distinct evolutionary rates of phenotypic diversification in internally fertilizing birds, mammals, reptiles, and insects 18,19,[37][38][39][40] . These findings suggest that sperm components can evolve independently.…”
mentioning
confidence: 99%
“…Comparative studies of the rates of evolutionary divergence in components of sperm cells suggest that different components are evolving independently; among lizards and snakes the length of the midpiece appears to be diverging faster than that of the flagella [ 68 , 69 ]. Similarly, among bovids and cervids, the length of the head and the midpiece are diverging faster than the length of the flagella [ 10 ]. Among Drosophila species that produce two sperm cell types, those that affect fertilization and those that do not, the rate of evolutionary divergence in head length is greater than flagella length for fertile sperm while the reverse is true of the non-fertile sperm morph [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and divergent evolution is widely recognized as being a signature of strong directional selection. For example, there is now compelling evidence to show that sexual selection is responsible for the rapid and divergent evolution of secondary sexual traits in males that serve as weapons or ornaments in the competition for access to females [ 5 , 6 , 7 , 8 , 9 , 10 ]. Arguably, one of the most significant advances in our understanding of sexual selection since Darwin [ 5 ], was Geoff Parker’s [ 11 ] insight that sexual selection would continue after mating [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, theory suggests that higher levels of sperm competition may result in an increase in both the overall length of sperm and the length of each section ( Briskie et al, 1997 ; Fitzpatrick et al, 2009 ); this covariance could be the result of genetic or other functional and mechanistic constraints. However, recent research has found that sperm sections can display distinct rates of phenotypic diversification ( Immler et al, 2012 ; Rowe et al, 2015 ; Kahrl et al, 2019 ; Fitzpatrick et al, 2020 ; Friesen et al, 2020 ; Reuland et al, 2021 ), suggesting that the independent evolution of sperm sections is possible ( Kahrl et al, 2022 ), though this is poorly understood in many taxa. Thus, it is important to consider variation in the length of each section independently.…”
Section: Introductionmentioning
confidence: 99%